Traumatic buccal fat pad herniation in an infant - Giulia De Giorgi; Rossella Angotti; Giulia Fusi; Lorenzo Salerni; Mario Messina; Francesco Molinaro (Elsevier, 2019)
Traumatic herniation of buccal fat pad (BFP) is very rare, usually seen in young children, from 5 months to 12 years of age. A minor injury or perforation of the buccinator muscle and buccal mucosa can cause the extrusion of the buccal fat pad into the oral cavity. A differential diagnosis is very important but a history of trauma, an absence of masses before the accident, anatomical site and fatty appearance should suggest the correct diagnosis. The treatment options are usually excision or repositioning of the herniated fat. For the present case report, a 7 month-old boy, diagnosed with traumatic buccal fat pad herniation, was successfully treated with surgical excision. Keywords: Buccal fat pad, Herniation, Children, Trauma